Common Fixed Points of Weak Contractions in Cone Metric Spaces. (10th May 2012) - Ding, Hui-Sheng; Kadelburg, Zoran; Karapınar, Erdal; Radenović, Stojan
Abstract : Results on common fixed points of mappings in cone metric spaces under weak contractive conditions (B. S. Choudhury and N. Metiya (2010)) are unified and generalized. Also, cone metric versions of some other related results on weak contractions are proved. Examples show that our results are different than the existing ones.